Medullary colonic carcinoma with microsatellite instability has lower survival compared with conventional colonic adenocarcinoma with microsatellite instability - Miguel A. Gómez-Álvarez; Leonardo S. Lino-Silva; Rosa A. Salcedo-Hernández; Alejandro Padilla-Rosciano; Erika B. Ruiz-García; Horacio N. López-Basave; German Calderillo-Ruiz; José M. Aguilar-Romero; Jorge A. Domínguez-Rodríguez; Ángel Herrera-Gómez; Abelardo Meneses-García (Gastroenterology Review)
Introduction: Colorectal medullary carcinoma (MC) is a rare subtype of poorly differentiated adenocarcinoma (PDA) with unclear prognostic significance. Microsatellite instable (MSI) colorectal carcinomas have demonstrated better prognosis in clinical stage II. Aim: To analyze the survival and clinicopathological characteristics of MCs versus PDAs with MSI in clinical stage III. Material and methods: We studied 22 cases of PDAs with MSI versus 10 MCs. Results : Of the 10 MCs, 7 patients were men; the mean age was 57.8 ±5.6 years. The mean tumor size was 9.6 ±4.1 cm, and the primary site was the right colon in 9; 7 patients showed lymph node metastases (LNM) and lymphovascular invasion (LVI). Of the 22 PDA cases, 12 (54.5%) were women with a mean age of 75 ±16.1 years. The mean tumor size was 6.4 ±3.2 cm. Twelve (54.5%) presented in the right colon, 21 (95.5%) showed LNM and 7 (31.8%) LVI. Follow-up was 32 ±8 months, with a 5-year overall survival of 42.9% for MCs and 76.6% for PDAs (p = 0.048). Univariate analysis found local recurrence (p = 0.001) and medullary subtype (p = 0.043) associated with lower survival. Conclusions : Medullary carcinomas were of greater tumor size and associated with more LVI and worse survival versus PDAs with MSI in stage III.